(untitled) (TAJ: Journal of Teachers Association, 2018)
This was a cross sectional type of descriptive study which was conducted in four villages of Puthia Upozila of Rajshahi district. A preformed interview schedule was used to collect data from a purposively selected sample of 518 respondents. The study revealed that 42.9% children had 1st degree malnutrition, about 19.5% children had 2nd malnutrition and 1.7% had 3rd degree malnutrition. The mean age of the children was 3.45 ± SD 1.33 years. Out of 518 respondents 74.7% had monthly income of Tk. 5000/- or less and 25.3% respondents had monthly income of Tk. 5001/- and above. The mean monthly was Tk. 5039/- ± SD 3869.36.Undernutrition was more in female children (70.1%) than male children (51.2%). In large family size under nutrition were more (68.4%) in comparison to small family size (61.4%). The study would be helpful in future community survey on nutritional status of under five children and in formulating effective national nutrition health program and facilitating their effective implementation. TAJ 2012; 25: 13-16